Increasing Awareness and Healthy Living Practices in Hypertension Prevention among PKK Mothers in Sragen Regency - Aris Widiyanto; Prissy Verasita; Tidy Orchida; Hakim Anasulfalah; Trisakti Halimah Delimasari; Rahma Yuniarti (Universitas STRADA Indonesia, 2025)
Hypertension, a medical condition characterized by high blood pressure, is the most widespread public health problem in the world, with approximately 1.13 billion people worldwide living with hypertension, with prevalence increasing with age and lifestyle changes. PKK mothers have a very important role in efforts to prevent health problems in the community, especially at the village or kelurahan level. The method used in this community service is health education about hypertension using leaflet and video media through the stages of distribution of knowledge questionnaires about (before education), education or counseling, distribution of knowledge questionnaires about hypertension (after education). The implementation of activities took place in Kauman, Masaran, Sragen Regency, Central Java Province. Results The counseling provided on healthy living practices in the prevention of hypertension proved effective in increasing the level of knowledge of participants. There was a significant increase in knowledge scores after counseling, where the majority of participants reached the high knowledge category.